Wood preservation - Richardson, Barry A., 1937- (Construction Press, 1978)
The new edition of this comprehensive study of national and international research and application into wood preservation is both well detailed and broad in coverage. The text covers the history of preservation: the anatomy of timbers and their breakdown, preservation principles, materials and methods.